A comparison between interactions of triglyceride oil and mineral oil with proteins and their ability to reduce cleanser surfactant‐induced irritation. (13th April 2015) - Mukherjee, S.; Yang, L.; Vincent, C.; Lei, X.; Ottaviani, M. F.; Ananthapadmanabhan, K. P.
Synopsis Objective Skin irritation in personal cleansing has been correlated with surfactant binding with stratum corneum proteins. Polar and non‐polar oils are increasingly being used in cleansing formulations which contain high (10–15%) level of anionic and non‐ionic surfactants. However, the effects of oils in modulating skin damage from a cleansing product have not been studied in any detail. The objectives of this study are to determine whether low‐viscosity polar and non‐polar oils differ in their ability to reduce surfactant‐induced skin irritation and, if so, how it might be related to their interactions with proteins. Methods Surfactant‐induced skin irritation was measured by a 14‐day in vivo cumulative patch irritation test. The methodology was similar to the well‐known soap chamber test. Surfactant interactions with the water‐soluble protein, bovine serum albumin (BSA), in the presence of oils were measured by conductometric titration. The effects of low‐viscosity polar and non‐polar oils on stratum corneum protein dynamics in the sulfhydryl group region were studied by electron paramagnetic resonance (EPR) using the covalently bound spin‐label 3‐maleimido‐proxyl (5‐MSL). EPR measurements were performed with stratum corneums obtained from discarded skins of 3‐ to 4‐week‐old female pigs. Simulation of the complex spectra provided insights on the environment and mobility of the protein‐bound spin label. Results Addition of 1% polar sunflower seed oil (viscosity 42 centipoise) reduced in vivo irritation of 1% sodium lauryl ether sulphate with two ethoxylate/cocamidopropyl betaine (SLES/CAPB) by 20%, whereas 1% non‐polar mineral oil (viscosity 15 centipoise) had no effect. Polar oil glyceryl trioleate (a major component in sunflower seed oil) at 10% level reduced surfactant binding to BSA protein in water by 40%, whereas the non‐polar oil dodecane (a major component of mineral oil) at a similar level did not have any effect. The mobility of the spin label in a dry corneum was very low and was increased significantly with the addition of water and glycerol trioleate but less so with mineral oil. Conclusion Sunflower seed oil reduces surfactant‐induced in vivo skin irritation more than mineral oil. This is possibly due to stronger interaction of polar oil with proteins, thus protecting it from surfactant binding.